2021
DOI: 10.1194/jlr.ra120000974
|View full text |Cite
|
Sign up to set email alerts
|

Lipid signature of advanced human carotid atherosclerosis assessed by mass spectrometry imaging

Abstract: Carotid atherosclerosis is a risk factor for ischemic stroke, one of the main causes of mortality and disability worldwide. The disease is characterized by plaques, heterogeneous deposits of lipids, and necrotic debris in the vascular wall, which grow gradually and may remain asymptomatic for decades. However, at some point a plaque can evolve to a high-risk plaque phenotype, which may trigger a cerebrovascular event. Lipids play a key role in the development and progression of atherosclerosis, but the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
(62 reference statements)
4
8
0
Order By: Relevance
“… 20) Lehti et al 21) analyzed the ultrastructure of the accumulated lipids in endarterectomized human carotid atherosclerotic plaques using three-dimensional electron microscopy and revealed that apolipoprotein B is their main protein component, indicating their origin from LDL, intermediate-density lipoprotein, very LDL, lipoprotein (a), or chylomicron remnants. Moerman et al 22) visualized the distribution of approximately 200 different lipid signals in endarterectomized human carotid atherosclerotic plaques using matrix-assisted laser desorption/ionization mass spectrometry imaging, and revealed that TGs were spatially correlated to areas containing the coagulation protein fibrin, providing a possible marker for intraplaque bleeding. Although the proatherogenic mechanisms associated with TGs and TG-rich lipoproteins seem rather complicated and need to be further explored, it may be reasonable to measure non-fasting TG levels, which may reflect the levels of TG-rich lipoproteins and the remnants.…”
Section: Discussionmentioning
confidence: 99%
“… 20) Lehti et al 21) analyzed the ultrastructure of the accumulated lipids in endarterectomized human carotid atherosclerotic plaques using three-dimensional electron microscopy and revealed that apolipoprotein B is their main protein component, indicating their origin from LDL, intermediate-density lipoprotein, very LDL, lipoprotein (a), or chylomicron remnants. Moerman et al 22) visualized the distribution of approximately 200 different lipid signals in endarterectomized human carotid atherosclerotic plaques using matrix-assisted laser desorption/ionization mass spectrometry imaging, and revealed that TGs were spatially correlated to areas containing the coagulation protein fibrin, providing a possible marker for intraplaque bleeding. Although the proatherogenic mechanisms associated with TGs and TG-rich lipoproteins seem rather complicated and need to be further explored, it may be reasonable to measure non-fasting TG levels, which may reflect the levels of TG-rich lipoproteins and the remnants.…”
Section: Discussionmentioning
confidence: 99%
“…It was established to correlate with the thrombus fragments like coagulation protein fibrin, diacylglycerols and triacylglycerols. 129 The targeted mass spectrometric analysis first reported the presence of oxidized phosphatidylinositol species in human atherosclerotic plaques and oxidized human LDL. 130 Surendran et al identified deferred concentration and distribution of oxylipins in the LDL, depending on the varying degree of oxidative stress.…”
Section: Mass Spectrometry-based Metabolomics and Its Recent Advancem...mentioning
confidence: 99%
“…As mentioned, ceramide species can induce endothelial dysfunction and increase vascular permeability by promoting oxidative stress, inflammation and by reducing the production of nitric oxide (NO) [40]. Therefore, ceramides are important regulators of tissue metabolism and play vital roles in pathophysiological processes with implications in cardiometabolic disease such as ATS [41], inflammation, obesity, NAFLD [42], pancreatic ß-cell dysfunction, T2DM [43], and cancer [44].…”
Section: Ceramides In Nafld-ats Developmentmentioning
confidence: 99%